Long-range conjugated organic / inorganic gas separation membrane and preparation method thereof

The preparation of organic/inorganic gas separation membrane with planar conjugated framework is solved through microwave assistance, and the interfacial compatibility and stability of organic/inorganic hybrid membranes is solved, and the efficient CO2/N2 gas separation performance is achieved, and excellent mechanical properties are achieved. and environmental adaptability.

CN119318890AActive Publication Date: 2025-01-17SHENHUA SHENDONG COAL GRP +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411592031.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-17
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing organic/inorganic hybrid films face challenges such as filler and substrate interface compatibility, uniform dispersion and membrane stability in gas separation applications, and it is difficult to effectively deal with complex changes in waste gas temperature and humidity, affecting its separation performance.

Method used

Using microwave-assisted preparation of halogen functional carbon nanotubes mixed with long-range conjugated bromine functional blocks and alkynium functional blocks, the organic/inorganic composite materials with planar conjugated skeletons and uniform pore structures were prepared through cross-coupling reactions, and through natural settlement and vacuum drying to prepare defect-free organic/inorganic gas separation membranes to enhance mechanical flexibility and environmental tolerance.

Benefits of technology

It realizes effective adsorption and separation of high-performance CO2/N2 two-component mixed gas, with a wide specific surface area, uniform pore size, ideal adsorption capacity, excellent mechanical flexibility and environmental tolerance, and the preparation process is simple and the conditions are mild.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318890A_ABST
    Figure CN119318890A_ABST
Patent Text Reader

Abstract

The invention provides a long-range conjugated organic / inorganic gas separation membrane and a preparation method thereof, and the method comprises the following steps: S1, placing a carbon nanotube, a reaction solvent and halogen in a microwave reaction kettle to prepare a halogen functionalized carbon nanotube; s2, uniformly dispersing a long-range conjugated bromine functional building block, an alkyne functional building block, a catalyst and the bromine-functionalized carbon nanotube obtained in the step S1 in a reaction solvent, and preparing a rigid skeleton structure composite material through a cross-coupling reaction; and S3, preparing the organic / inorganic gas separation membrane with the long-range conjugated structure from the composite material obtained in S2 through natural sedimentation and vacuum drying. The prepared gas separation membrane not only has a series of advantages of long-range conjugated structure, wide specific surface area, uniform pore size, ideal adsorption capacity and the like, but also has excellent mechanical flexibility and environmental tolerance, the preparation process is simple, the conditions are mild, and the gas separation membrane is a high-performance gas separation material with wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of in-situ polymerization gas separation membranes, and in particular to a long-range conjugated organic / inorganic gas separation membrane and a preparation method thereof. Background Art

[0002] Understanding of air pollution should not be limited to the environmental and health problems it causes, but should focus on the impact and feedback between air pollution and climate change, as well as the study of the synergistic benefits of air pollution control and greenhouse gas emission reduction. A large number of studies have shown that there is a synergistic effect between air pollution control and greenhouse gas emission reduction: (1) Air pollutants and greenhouse gases have the same origin. Specifically, the combustion of fossil fuels during production and daily activities produces a large amount of particulate matter (PM) and carbon dioxide (CO 2 ) are released into the atmosphere together. (2) Many air pollution control measures are also effective measures to reduce greenhouse gas emissions, such as the renewal and optimization of energy structure, the adjustment of industrial structure, energy conservation and consumption reduction, etc. Therefore, air pollutant control measures and greenhouse gas emission reduction measures are intertwined, interact and complement each other. The close relationship between the two guides the design and development of co-capture materials.

[0003] As an important carbon-containing compound, carbon dioxide adsorption and separation technology plays a vital role in optimizing resource utilization and also provides important support for the development of fossil energy. 2 The high oxidation state, thermodynamic stability, kinetic inertia, and significantly different molecular diameters of PM present significant challenges for their synergistic deep processing. Membrane separation technology is the most effective and direct method for intercepting PM and separating multiple gas mixtures. It helps to quickly capture and separate gases with low energy consumption, while achieving integration and automation in relatively compact separation units. However, the composition, proportion, and environmental conditions of exhaust gases at the end of industrial pipelines can vary greatly. Therefore, existing membrane processes often have difficulty in coping with the complex and changing challenges brought about by factors such as exhaust gas temperature and humidity.

[0004] Organic / inorganic hybrid membranes are considered a promising method for PM and CO 2Synergistic capture technologies are emerging as they effectively combine the processing advantages of inorganic templates with the design flexibility of porous organic polymer fillers. In the design of gas separation membranes, research focuses on optimizing the structure and preparation process of the membranes, forming composite structures by doping highly selective fillers in flexible substrates, optimizing the physical and chemical properties of the membranes, and improving the gas separation performance. In the field of gas separation, conjugated microporous polymers (CMPs) have significant advantages and great application potential as fillers for hybrid membranes. CMPs have special pore structures and high specific surface areas, providing ample gas channels and promoting accelerated separation processes. Due to their tunable chemical composition and functional sites, CMPs can selectively adsorb specific gases, thereby enhancing the binding specificity and affinity of the membrane. By organically combining with flexible substrates, CMPs enhance mechanical strength and durability while improving membrane separation performance, making them ideal for efficient and sustainable gas separation.

[0005] However, the practical application of organic-inorganic hybrid membranes is hampered by challenges such as interfacial compatibility between fillers and substrates, uniform dispersion of fillers, and concerns about membrane stability and processability. With the continuous development and cross-integration of the field of materials science, interfacial polymerization technology combines the synergistic effects of interfacial chemistry and polymerization chemistry, and can be combined with a variety of materials (such as element doping, metal coordination) to form a composite system, thereby optimizing the performance and application range of composite materials. Compared with traditional polymerization systems, interfacial polymerization technology combined with interfacial effects can not only regulate the grafting density, grafting configuration and grafting efficiency of polymers on the substrate, but also significantly improve the mechanical stability and processing flexibility of separation membranes. The active sites on the substrate surface can enhance the adsorption energy of reactant molecules, allowing them to be activated by two or more different active sites at the same time. This greatly reduces the compatibility issues of heterogeneous interfaces at the micro-nano scale, which is conducive to directional and uniform growth on the interface, making it highly attractive for the manufacture of high-value functional materials. Summary of the invention

[0006] Purpose of the invention: To meet the demand for mixed-component gas separation materials, the present invention adopts microwave-assisted preparation of halogen-functionalized carbon nanotubes, which are mixed with long-range conjugated bromine functional building blocks and alkyne functional building blocks and cross-coupled under metal catalysts to prepare organic / inorganic composite materials (the conventional expression of organic polymer growth on inorganic materials is: organic / inorganic) with a planar conjugated skeleton and uniform pore structure, and prepares surface defect-free organic / inorganic gas separation membranes by natural sedimentation and vacuum drying. The gas separation membranes not only have a series of advantages such as long-range conjugated structure, wide specific surface area, uniform pore size, ideal adsorption capacity, etc., but also have excellent mechanical flexibility and environmental tolerance, simple preparation process, mild conditions, and are a high-performance gas separation material with broad application prospects.

[0007] The present invention provides a long-range conjugated organic / inorganic gas separation membrane and a preparation method thereof. The method comprises the following steps:

[0008] Step S1, preparing halogen-functionalized carbon nanotubes: pretreating carbon nanotubes with a mixed solution of concentrated nitric acid and concentrated sulfuric acid (cleaning the surface of the carbon nanotubes to remove surface impurities and increase surface activity, the carbon nanotubes are generally 15 to 35 mL of carbon nanotubes), dispersing the treated carbon nanotubes in a reaction solvent, slowly dropping halogen and ultrasonically dispersing to obtain a mixture, transferring the mixture to a microwave reaction tube, and preparing halogen-functionalized carbon nanotubes in a microwave reactor;

[0009] Step S2, preparing a rigid skeleton structure composite material: fully mixing the halogen functionalized carbon nanotubes, the long-range conjugated bromine functional building blocks, the alkyne functional building blocks and the catalyst in a reaction solvent, and performing solvent replacement and Soxhlet extraction to clean the rigid skeleton structure composite material after a constant temperature continuous reaction;

[0010] Step S3, preparing a long-range conjugated organic / inorganic gas separation membrane: the thoroughly cleaned composite material is subjected to natural sedimentation and vacuum drying to prepare a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid framework and uniform pore size.

[0011] In step S1, the carbon nanotubes are at least one of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes, the volume ratio of the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:1 to 3:1, and the amount of the carbon nanotubes is 0.3 to 1.0 g.

[0012] In step S1, the reaction solvent is at least one of tetrachloromethane, dichloromethane, N,N-dimethyl sulfoxide, and N-methylpyrrolidone, the amount of the reaction solvent is 15 to 35 mL, the halogen is at least one of chlorine, bromine, and iodine, and the amount of the halogen is 1 to 4 mL.

[0013] In step S1, the output power of the microwave reactor is 100-300 W, the reaction temperature is 70-150° C., and the reaction time is 10-60 minutes.

[0014] In step S2, the reaction solvent is at least one of toluene, N,N-dimethylformamide, 1,2-dichloroethane, and tetrahydrofuran, the reaction solvent is mixed with triethylamine, the volume ratio of the reaction solvent to triethylamine is 1:1 to 3:1, the catalyst is tetrakistriphenylphosphine palladium and cuprous iodide, and the molar ratio of the two catalysts is 1:5 to 1:15.

[0015] In step S2, the long-range conjugated bromine functional building block is at least one of 1,6-dibromopyrene, 2,7-dibromopyrene, 1,8-dibromopyrene, and 1,3,6,8-tetrabromopyrene, and the reaction unit molar ratio of the long-range conjugated bromine functional building block to the alkyne functional building block is 1:1 to 2:1.

[0016] In step S2, the reaction temperature of the constant temperature continuous reaction is 80-100° C., and the reaction time is 48-84 hours.

[0017] In step S2, the solvents used in the solvent replacement are dichloromethane, chloroform, acetone, deionized water and methanol in sequence, and the solvent used in the Soxhlet extraction is at least one of methanol, chloroform and dichloromethane.

[0018] In step S3, the vacuum drying temperature is 40 to 80°C, the vacuum degree is less than or equal to -0.09 MPa, and the drying time is 6 to 24 hours.

[0019] The present invention also provides a long-range conjugated organic-inorganic gas separation membrane, which is prepared by the method and can be applied to CO 2 / N 2 Effective adsorption and separation under two-component mixing conditions.

[0020] Beneficial effects: The present invention provides a long-range conjugated organic / inorganic gas separation membrane and a preparation method thereof. Halogen-functionalized carbon nanotubes are prepared by microwave-assisted method, mixed with functional building blocks and structural building blocks, and cross-coupled under metal catalyst to prepare a stable composite material with continuous rigid structure and uniform pore size. The long-range conjugated organic / inorganic gas separation membrane is prepared by natural sedimentation and vacuum drying. The specific surface area of ​​the hybrid membrane is 184-301m 2 / g, pore size is 1.67-2.33nm, CO 2 The adsorption capacity is 1.7-2.8mmol / g, CO 2 / N 2 The separation selectivity is 12-54. It not only has a series of advantages such as long-range conjugated structure, wide specific surface area, uniform pore size, ideal adsorption capacity, but also has excellent mechanical flexibility and environmental tolerance. The preparation process is simple and the conditions are mild. It is a high-performance gas separation material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0022] Figure 1 is a scanning electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 1.

[0023] Figure 2 is a transmission electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 1.

[0024] Figure 3 This is a Fourier transform infrared spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 1.

[0025] Figure 4 This is the powder X-ray diffraction spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 1.

[0026] Figure 5 3 is a nitrogen adsorption-desorption isotherm curve of the long-range conjugated organic / inorganic gas separation membrane in Example 1.

[0027] Figure 6 is a scanning electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 2.

[0028] Figure 7 is a transmission electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 2.

[0029] Figure 8 This is a Fourier transform infrared spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 2.

[0030] Fig. 9 This is the powder X-ray diffraction spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 2.

[0031] Fig.10 This is a nitrogen adsorption-desorption isotherm curve of the long-range conjugated organic / inorganic gas separation membrane in Example 2.

[0032] Fig.11 is a scanning electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 3.

[0033] Fig.12 is a transmission electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 3.

[0034] Fig.13 This is a Fourier transform infrared spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 3.

[0035] Fig.14 This is the powder X-ray diffraction spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 3.

[0036] Fig.15 This is a pore size distribution curve of the long-range conjugated organic / inorganic gas separation membrane in Example 3.

[0037] Fig.16 is a scanning electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 4.

[0038] Fig.17 is a transmission electron microscope image of the long-range conjugated organic / inorganic gas separation membrane in Example 4.

[0039] Fig.18 This is a Fourier transform infrared spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 4.

[0040] Fig.19 This is the powder X-ray diffraction spectrum of the long-range conjugated organic / inorganic gas separation membrane in Example 4.

[0041] Fig. 20 This is a pore size distribution curve of the long-range conjugated organic / inorganic gas separation membrane in Example 4.

[0042] Fig.21 It is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0043] Example 1

[0044] like Fig.21 As shown, this embodiment provides a method for preparing a long-range conjugated organic / inorganic gas separation membrane, comprising the following steps:

[0045] S11. Preparation of halogen-functionalized carbon nanotubes: 0.5 g of single-walled carbon nanotubes were pretreated in a mixture of concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) and dispersed in carbon tetrachloride. 2 mL of bromine was slowly added dropwise under ultrasonic conditions, and the mixture was transferred to a microwave reaction tube and sealed. The reaction was carried out in a microwave reactor (output power 150 W, reaction temperature 80 ° C, reaction time 30 minutes) to prepare halogen-functionalized carbon nanotubes;

[0046] S12. Preparation of a rigid skeleton structure composite material: Place a mixture of halogen-functionalized carbon nanotubes prepared in S11, 1,3,6,8-tetrabromopyrene, 1,3,5-triethynylbenzene (molar ratio 1:1) and anhydrous N,N-dimethylformamide in a round-bottom flask. Add dry triethylamine (the volume ratio of N,N-dimethylformamide to triethylamine is 2:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:10) and react at 90°C under argon for 72 hours. Replace the solvent with dichloromethane, acetone, deionized water and methanol in turn, and further Soxhlet extraction with methanol for 48 hours to prepare a rigid skeleton structure composite material;

[0047] S13. Preparation of long-range conjugated organic / inorganic gas separation membrane: The composite material prepared in S12 was subjected to natural sedimentation and vacuum drying (drying temperature 60°C, vacuum degree -0.09MPa, drying time 12 hours) to prepare a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid skeleton and uniform pore size, with a specific surface area of ​​301m 2 / g, and the average pore size is 1.67nm.

[0048] Figure 1 This is a scanning electron microscope image of the gas separation membrane obtained in Example 1, which shows that the material is a three-dimensional network structure in which the porous CMPs adsorption active layer uniformly wraps the carbon nanotubes.

[0049] Figure 2 This is a transmission electron microscope image of the gas separation membrane obtained in Example 1, which shows that the material is a core-shell structure with CMPs as a porous shell and carbon nanotubes as a supporting core, and the thickness of the CMPs layer is 4-8nm.

[0050] Figure 3 This is a Fourier transform infrared spectrum of the gas separation membrane obtained in Example 1, which shows that the material structure has the stretching vibration of the terminal alkyne (-C≡CH) and the stretching vibration of C=C and C≡C.

[0051] Figure 4 The powder X-ray diffraction pattern of the gas separation membrane obtained in Example 1 shows that the material has a diffraction peak (18°) representing an amorphous CMPs and diffraction peaks (28° and 43°) representing carbon nanotubes of (002) and (100) crystal planes.

[0052] Figure 5 N is the N of the gas separation membrane obtained in Example 1 2 The adsorption-desorption isotherm curves show that the material has a large specific surface area and a hierarchical porous structure.

[0053] In the figure, Transmittance represents transmittance, Wavenumber represents wave number, Intensity represents intensity, 2Theta represents 2θ diffraction angle, Quantity Adsorbed represents adsorption amount, and Relative pressure represents relative pressure.

[0054] Example 2

[0055] This embodiment provides a method for preparing a long-range conjugated organic / inorganic gas separation membrane, comprising the following steps:

[0056] S21. Preparation of halogen-functionalized carbon nanotubes: 0.3 g of double-walled carbon nanotubes were pretreated in a mixture of concentrated nitric acid and concentrated sulfuric acid (volume ratio 2:1) and dispersed in dichloromethane. 2 mL of iodine was slowly added dropwise under ultrasonic conditions, and the mixture was transferred to a microwave reaction tube and sealed. The reaction was carried out in a microwave reactor (output power 300 W, reaction temperature 150 ° C, reaction time 60 minutes) to prepare halogen-functionalized carbon nanotubes;

[0057] S22. Preparation of a rigid skeleton structure composite material: Place a mixture of halogen-functionalized carbon nanotubes prepared in S21, 1,6-dibromopyrene, 1,3,5-triethynylbenzene (molar ratio 3:2) and anhydrous toluene in a round-bottom flask. Add dry triethylamine (the volume ratio of toluene to triethylamine is 1:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:15) and react at 100°C under argon for 48 hours. Replace the solvent with chloroform, acetone, deionized water and methanol in turn, and further perform Soxhlet extraction with chloroform for 48 hours to prepare a rigid skeleton structure composite material;

[0058] S23. Preparation of long-range conjugated organic / inorganic gas separation membrane: The composite material prepared in S22 was subjected to natural sedimentation and vacuum drying (drying temperature 40°C, vacuum degree -0.08MPa, drying time 24 hours) to prepare a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid skeleton and uniform pore size, with a specific surface area of ​​279m 2 / g, and the average pore size is 1.88nm.

[0059] Figure 6 This is a scanning electron microscope image of the gas separation membrane obtained in Example 2, which shows that the material is a three-dimensional network structure in which the porous CMPs adsorption active layer uniformly wraps the carbon nanotubes.

[0060] Figure 7 This is a transmission electron microscope image of the gas separation membrane obtained in Example 2, which shows that the material is a core-shell structure with CMPs as a porous shell and carbon nanotubes as a supporting core, and the thickness of the CMPs layer is 4-8nm.

[0061] Figure 8 This is a Fourier transform infrared spectrum of the gas separation membrane obtained in Example 2, which shows that the material structure has the stretching vibration of the terminal alkyne (-C≡CH) and the stretching vibration of C=C and C≡C.

[0062] Fig. 9 The powder X-ray diffraction pattern of the gas separation membrane obtained in Example 2 shows that the material has a diffraction peak (18°) representing an amorphous CMPs and diffraction peaks (28° and 43°) representing carbon nanotubes of (002) and (100) crystal planes.

[0063] Fig.10 is the N of the gas separation membrane obtained in Example 22 The adsorption-desorption isotherm curves show that the material has a large specific surface area and a hierarchical porous structure.

[0064] Example 3

[0065] This embodiment provides a method for preparing a long-range conjugated organic / inorganic gas separation membrane, comprising the following steps:

[0066] S31. Preparation of halogen-functionalized carbon nanotubes: 1.0 g of multi-walled carbon nanotubes were pretreated in a mixture of concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:2) and dispersed in N,N-dimethyl sulfoxide. Chlorine was slowly introduced under ultrasonic conditions, and the mixture was transferred to a microwave reaction tube and sealed. The reaction was carried out in a microwave reactor (output power of 100 W, reaction temperature of 70 ° C, reaction time of 10 minutes) to prepare halogen-functionalized carbon nanotubes;

[0067] S32. Preparation of a rigid skeleton structure composite material: Place a mixture of halogen-functionalized carbon nanotubes prepared in S31, 2,7-dibromopyrene, 1,3,5-triethynylbenzene (molar ratio 4:3) and anhydrous 1,2-dichloroethane in a round-bottom flask. Add dry triethylamine (1,2-dichloroethane to triethylamine volume ratio of 3:2), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:5) and react at 80°C under argon for 84 hours. Replace the solvent with chloroform, dichloromethane, acetone, deionized water and methanol in turn, and further perform Soxhlet extraction with dichloromethane for 48 hours to prepare a rigid skeleton structure composite material;

[0068] S33. Preparation of long-range conjugated organic / inorganic gas separation membrane: The composite material prepared in S32 was subjected to natural sedimentation and vacuum drying (drying temperature 80°C, vacuum degree -0.07MPa, drying time 8 hours) to prepare a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid skeleton and uniform pore size, with a specific surface area of ​​267m 2 / g, and the average pore size is 1.95nm.

[0069] Fig.11 This is a scanning electron microscope image of the gas separation membrane obtained in Example 3, which shows that the material is a three-dimensional network structure in which the porous CMPs adsorption active layer uniformly wraps the carbon nanotubes.

[0070] Fig.12 This is a transmission electron microscope image of the gas separation membrane obtained in Example 3, which shows that the material is a core-shell structure with CMPs as a porous shell and carbon nanotubes as a supporting core, and the thickness of the CMPs layer is 4-8nm.

[0071] Fig.13 This is the Fourier transform infrared spectrum of the gas separation membrane obtained in Example 3, indicating that the material structure has the stretching vibration of the terminal alkyne (-C≡CH) and the stretching vibration of C=C and C≡C.

[0072] Fig.14 The powder X-ray diffraction pattern of the gas separation membrane obtained in Example 3 shows that the material has a diffraction peak (18°) representing an amorphous CMPs and diffraction peaks (28° and 43°) representing carbon nanotubes of (002) and (100) crystal planes.

[0073] Fig.15 This is the pore size distribution curve of the gas separation membrane obtained in Example 3, indicating that the material has a wide specific surface area and a hierarchical porous structure. In the figure, Pore Volume represents the pore volume, and Pore Width represents the pore size.

[0074] Example 4

[0075] This embodiment provides a method for preparing a long-range conjugated organic / inorganic gas separation membrane, comprising the following steps:

[0076] S41. Preparation of halogen-functionalized carbon nanotubes: 1.0 g of single-walled carbon nanotubes were pretreated in a mixture of concentrated nitric acid and concentrated sulfuric acid (volume ratio 1:1) and dispersed in N-methylpyrrolidone, bromine was slowly introduced under ultrasonic conditions, and the mixture was transferred to a microwave reaction tube and sealed. The reaction was carried out in a microwave reactor (output power of 200 W, reaction temperature of 140 ° C, reaction time of 20 minutes) to prepare halogen-functionalized carbon nanotubes;

[0077] S42. Preparation of a rigid skeleton structure composite material: Place a mixture of halogen-functionalized carbon nanotubes prepared in S41, 1,8-dibromopyrene, 1,3,5-triethynylbenzene (molar ratio: 2) and anhydrous tetrahydrofuran in a round-bottom flask. Add dry triethylamine (the volume ratio of tetrahydrofuran to triethylamine is 2:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio 1:12) and react at 85°C under argon for 60 hours. Replace the solvent with chloroform, dichloromethane, acetone, deionized water and methanol in turn, and further perform Soxhlet extraction with acetone for 48 hours to prepare a rigid skeleton structure composite material;

[0078] S43. Preparation of long-range conjugated organic / inorganic gas separation membrane: The composite material prepared in S42 was subjected to natural sedimentation and vacuum drying (drying temperature 70°C, vacuum degree -0.06MPa, drying time 18 hours) to prepare a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid skeleton and uniform pore size, with a specific surface area of ​​263m 2 / g, and the average pore size is 1.99nm.

[0079] Fig.16 This is a scanning electron microscope image of the gas separation membrane obtained in Example 4, which shows that the material is a three-dimensional network structure in which the porous CMPs adsorption active layer uniformly wraps the carbon nanotubes.

[0080] Fig.17 This is a transmission electron microscope image of the gas separation membrane obtained in Example 4, which shows that the material is a core-shell structure with CMPs as a porous shell and carbon nanotubes as a supporting core, and the thickness of the CMPs layer is 4-8nm.

[0081] Fig.18 This is the Fourier transform infrared spectrum of the gas separation membrane obtained in Example 4, which shows that the material structure has the stretching vibration of the terminal alkyne (-C≡CH) and the stretching vibration of C=C and C≡C.

[0082] Fig.19 The powder X-ray diffraction pattern of the gas separation membrane obtained in Example 4 shows that the material has a diffraction peak (18°) representing an amorphous CMPs and diffraction peaks (28° and 43°) representing carbon nanotubes of (002) and (100) crystal planes.

[0083] Fig. 20 This is the pore size distribution curve of the gas separation membrane obtained in Example 4, indicating that the material has a broad specific surface area and a hierarchical porous structure.

[0084] Comparative Example 1 (using bromine structural building blocks and long-range alkyne functional building blocks)

[0085] The method of Example 1 is basically used to prepare an organic / inorganic gas separation membrane. The difference is that in this example, an alkyne functional building block with a long-range conjugated structure is selected to undergo a coupling reaction with a bromine structural building block to prepare a long-range conjugated composite material. Specifically, 0.5g of single-walled carbon nanotubes is placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) for pretreatment and dispersed in carbon tetrachloride, 2mL of bromine is slowly added dropwise under ultrasonic conditions, and the mixture is transferred to a microwave reaction tube and sealed. Halogen-functionalized carbon nanotubes are prepared by reacting in a microwave reactor (output power of 150W, reaction temperature of 80°C, reaction time of 30 minutes); a mixture of halogen-functionalized carbon nanotubes, 1,3,5-tribromobenzene, 1,3,6,8-tetraethynylpyrene (molar ratio 1:1) and anhydrous N,N-dimethylformamide is placed in a round-bottom flask. Add dry triethylamine (N,N-dimethylformamide and triethylamine volume ratio of 2:1), tetratriphenylphosphine palladium and cuprous iodide (molar ratio of 1:10) to react at 90℃ under argon for 72 hours. Replace the solvent with dichloromethane, acetone, deionized water and methanol in turn, and then perform Soxhlet extraction with methanol for 48 hours to prepare a composite material with a rigid skeleton structure; prepare a short-range conjugated organic / inorganic gas separation membrane with a partially rigid skeleton and uniform pore size by natural sedimentation and vacuum drying (drying temperature 60℃, vacuum degree -0.09MPa, drying time 12 hours), with a specific surface area of ​​291m 2 / g, and the average pore size is 1.73nm.

[0086] Comparative Example 2 (Using Short-Range Conjugated Bromine Functional Building Blocks)

[0087] The method of Example 2 is basically used to prepare an organic / inorganic gas separation membrane. The difference is that in this example, a bromine functional building block with a short-range conjugated structure is selected to undergo a coupling reaction with an alkyne structural building block to prepare a short-range conjugated composite material. Specifically, 0.3g of double-walled carbon nanotubes is placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio 2:1) for pretreatment and dispersed in dichloromethane, 2mL of iodine is slowly added dropwise under ultrasonic conditions, and the mixture is transferred to a microwave reaction tube and sealed. The reaction is carried out in a microwave reactor (output power of 300W, reaction temperature of 150°C, reaction time of 60 minutes) to prepare halogen-functionalized carbon nanotubes; a mixture of halogen-functionalized carbon nanotubes, 2,6-dibromonaphthalene, 1,3,5-triethynylbenzene (molar ratio of 3:2) and anhydrous toluene is placed in a round-bottom flask. Dry triethylamine (volume ratio of toluene to triethylamine is 1:1), tetratriphenylphosphine palladium and cuprous iodide (molar ratio of 1:15) are added and reacted at 100°C under argon for 48 hours. The solvent was replaced with chloroform, acetone, deionized water and methanol in turn, and chloroform was further used for Soxhlet extraction for 48 hours to prepare a composite material with a rigid skeleton structure; a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid skeleton and uniform pore size was prepared by natural sedimentation and vacuum drying (drying temperature 40°C, vacuum degree -0.08MPa, drying time 24 hours) with a specific surface area of ​​242m 2 / g, and the average pore size is 2.07nm.

[0088] Comparative Example 3 (Using Non-conjugated Bromine Functional Building Blocks)

[0089] The method of Example 3 is basically used to prepare an organic / inorganic gas separation membrane. The difference is that in this example, a non-conjugated bromine functional building block is selected to undergo a coupling reaction with an alkyne structural building block to prepare a short-range conjugated composite material. Specifically, 1.0 g of multi-walled carbon nanotubes is placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:2) for pretreatment and dispersed in N, N-dimethyl sulfoxide, chlorine is slowly introduced under ultrasonic conditions, and the mixture is transferred to a microwave reaction tube and sealed. The reaction is carried out in a microwave reactor (output power of 100 W, reaction temperature of 70 ° C, reaction time of 10 minutes) to prepare halogen-functionalized carbon nanotubes; a mixture of halogen-functionalized carbon nanotubes, 4,4'-dibromobiphenyl, 1,3,5-triethynylbenzene (molar ratio 4:3) and anhydrous 1,2-dichloroethane is placed in a round-bottom flask. Dry triethylamine (1,2-dichloroethane and triethylamine volume ratio of 3:2), tetratriphenylphosphine palladium and cuprous iodide (molar ratio of 1:5) were added to react at 80°C under argon for 84 hours. The solvent was replaced with chloroform, dichloromethane, acetone, deionized water and methanol in turn, and dichloromethane was further Soxhlet extracted for 48 hours to prepare a rigid skeleton structure composite material; a continuous rigid skeleton and a long-range conjugated organic / inorganic gas separation membrane with uniform pore size was prepared by natural sedimentation and vacuum drying (drying temperature 80°C, vacuum degree -0.07MPa, drying time 8 hours), with a specific surface area of ​​184m 2 / g, and the average pore size is 2.33nm.

[0090] Structural characterization and performance testing:

[0091] Scanning electron microscope observation: The microstructure of the conjugated microporous polymer-carbon nanotube composite filtration membrane was observed by field emission scanning electron microscope (model JSM-7900F, Japan Electronics). Figure 1 , Figure 6 , Fig.11 , Fig.16 ).

[0092] Transmission electron microscopy observation: The microstructure of the conjugated microporous polymer-carbon nanotube composite filtration membrane was observed by field emission transmission electron microscopy (model TECNI G2 TF20, FEI Company, the Netherlands). Figure 2 , Figure 7 , Fig.12 , Fig.17 ).

[0093] Functional group structure test: An infrared spectrometer (model VERTEX 70, Bruker, USA) was used to record the functional groups of the conjugated microporous polymer-carbon nanotube composite filter membrane ( Figure 3 , Figure 8 , Fig.13 , Fig.18 ).

[0094] Crystal structure test: An X-ray spectrometer (model D / Max-2400, Rigaku Corporation, Japan) was used to record the crystal structure of the conjugated microporous polymer-carbon nanotube composite filter membrane ( Figure 4 , Fig. 9 , Fig.14 , Fig.19 ).

[0095] Specific surface area test: A gas adsorption instrument (ASAP 2060, Micromeritics, USA) was used to measure the nitrogen adsorption isotherm at 77K ( Figure 5 , Fig.10 , Fig.15 , Fig. 20 ).

[0096] Carbon dioxide adsorption performance test: A gas adsorption instrument (ASAP 2020, Micromeritics, USA) was used to measure CO 2 Adsorption. High purity gas CO 2 (99.999%) was used for the adsorption measurements, while free space was measured with helium (99.999%). Adsorption isotherms were performed at 273 K (ice-water bath) and 298 K (water bath).

[0097] Calculation of CO2 / N2 separation selectivity based on single-component CO at 273K and 298K 2 and N 2 Adsorption isotherms and separation selectivity were calculated using the ideal solution adsorption theory model.

[0098] Experimental results: Figure 1 , Figure 6 , Fig.11 and Fig.16 As shown, the conjugated microporous polymer and the halogen functionalized carbon nanotubes are grown in situ through interfacial polymerization to form a core-shell structure composite material, which can realize that the CMPs porous adsorption active layer has a continuous rigid skeleton. In Example 1, the surface of the carbon nanotubes is uniformly coated with the conjugated microporous polymer, and there is no obvious carbon nanotube agglomeration and free conjugated microporous polymer, which shows the controllable synthesis of the composite material. With the porous adsorption active layer as the shell and the three-dimensional structure carbon nanotube as the core, the material maintains good gas flow and mass transfer efficiency while fully exposing the pore properties and adsorption sites.

[0099] like Figure 2 , Figure 7 , Fig.12 and Fig.17As shown, the conjugated microporous polymer and halogen-functionalized carbon nanotubes are mixed to prepare an organic / inorganic gas separation membrane, which can achieve template growth with carbon nanotubes as the core and the conjugated microporous polymer as the filler. The lattice stripes representing the (002) and (100) crystal planes of the carbon nanotubes and the conjugated microporous polymer representing the amorphous structure can be clearly observed. The thickness of the conjugated microporous polymer shell is about 4-8nm, indicating that the conjugated microporous polymer uses the carbon nanotubes as a template to achieve interfacial in situ polymerization, and the specific surface area and pore properties of the gas separation membrane are not affected during the growth process.

[0100] like Figure 3 , Figure 8 , Fig.13 and Fig.18 As shown in Figure 2, it can be observed that the signals corresponding to the C≡CH and C-Br bonds disappear, indicating that the Sonogashira coupling reaction has completely occurred. -1 The signals observed at 2200 cm-1 correspond to the stretching and bending vibration modes of the CH bonds in the benzene ring; -1 The signals observed at can be attributed to the stretching vibration of the -C≡C- bond, and the appearance of characteristic functional groups indicates the successful in situ polymerization of the conjugated microporous polymer on the carbon nanosurface.

[0101] like Figure 4 , Fig. 9 , Fig.14 and Fig.19 As shown, the diffraction pattern exhibits two peaks at 28° and 43°, corresponding to the (002) and (100) crystal planes of the carbon nanotubes, respectively, and the diffraction pattern shows a broad peak centered at 18°, indicating that the gas separation membrane is formed with an amorphous structure under kinetic control.

[0102] like Figure 5 , Fig.10 , Fig.15 and Fig. 20 As shown in the figure, the adsorption and desorption isotherms all show a similar trend, namely, a medium-pressure section where the nitrogen adsorption amount gradually increases and a high-pressure section where nitrogen is rapidly adsorbed. Combined with the pore size distribution curve, it shows that the gas separation membrane has a graded porous structure.

[0103] Table 1 compares the specific surface area, pore size, CO 2 Adsorption capacity and CO 2 / N 2 Separation selectivity test results. Examples 1-4 and Comparative Examples 1 and 2 have a higher specific surface area (184 m 2 / g-301m 2 / g) and a smaller pore size (1.67nm-2.33nm), because the carbon nanotube template used in the polymerization process does not affect the porous structure of the conjugated microporous polymer, thereby achieving full exposure and full expression of the porous structure; the specific surface area of ​​comparative example 3 is only 184m 2 / g, and the average pore size is 2.33nm, which is due to the disordered formation of pores caused by the flipping of non-conjugated functional building blocks.

[0104] Table 1

[0105]

[0106]

[0107] Long-range conjugated organic / inorganic gas separation membranes for CO 2 Adsorption capacity and CO 2 / N 2 Separation selectivity is highly correlated with specific surface area and average pore size. Examples 1-4 and Comparative Example 1 with ideal specific surface area have a high selectivity for CO 2 The adsorption capacity performance is above 2.4mmol / g for the two components CO 2 / N 2 The separation selectivity of the mixed gas was greater than 31, which truly achieved a balanced relationship between adsorption capacity and separation selectivity. Among them, Example 1 with the highest specific surface area and the smallest pore size performed best in the adsorption capacity and separation selectivity tests. 2 The adsorption capacity reached 2.8 mmol / g and the separation selectivity reached 54, which was much higher than that of the comparative examples 2–3 (CO 2 Adsorption capacity ≤2.0mmol / g, separation selectivity ≤26).

[0108] It can be seen that the technical solution proposed in the present invention enables the long-range conjugated organic / inorganic gas separation membrane to have a continuous rigid structure, a wide specific surface area, a narrow pore size, an ideal adsorption capacity and good separation selectivity, which is likely due to: (1) the use of halogen-functionalized carbon nanotubes as templates provides abundant nucleation sites for the interfacial polymerization growth of conjugated microporous polymers; (2) the design of the continuous rigid skeleton causes the structure to be in the same plane, reduces the disordered stacking and entanglement of molecular chains, and promotes the formation of a uniform and continuous pore structure; (3) the carbon nanotubes form a three-dimensional network structure through random weaving and arrangement, which greatly improves the unit gas throughput of the composite filtration membrane and improves the gas flow and mass transfer efficiency of the material; (4) by polymerizing the conjugated microporous polymer at the surface interface of the carbon nanotubes, the binding energy barrier is effectively broken and the active sites are fully exposed, which is conducive to the CO 2 Adsorption and separation provide suitable pore size and sufficient accommodation space.

[0109] The present invention provides a long-range conjugated organic / inorganic gas separation membrane and a preparation method thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a long-range conjugated organic / inorganic gas separation membrane, characterized in that: The following steps are involved: Step S1, preparing halogen-functionalized carbon nanotubes: pretreating carbon nanotubes with a mixed solution of concentrated nitric acid and concentrated sulfuric acid, dispersing the treated carbon nanotubes in a reaction solvent, slowly adding halogen and ultrasonically dispersing to obtain a mixture, transferring the mixture to a microwave reaction tube, and preparing halogen-functionalized carbon nanotubes in a microwave reactor; Step S2, preparing a rigid skeleton structure composite material: fully mixing the halogen functionalized carbon nanotubes, the long-range conjugated bromine functional building blocks, the alkyne functional building blocks and the catalyst in a reaction solvent, and performing solvent replacement and Soxhlet extraction to clean the rigid skeleton structure composite material after a constant temperature continuous reaction; Step S3, preparing a long-range conjugated organic / inorganic gas separation membrane: the thoroughly cleaned composite material is subjected to natural sedimentation and vacuum drying to prepare a long-range conjugated organic / inorganic gas separation membrane with a continuous rigid framework and uniform pore size.

2. The method according to claim 1, characterized in that In step S1, the carbon nanotubes are at least one of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes, the volume ratio of the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:1 to 3:1, and the amount of the carbon nanotubes is 0.3 to 1.0 g.

3. The method according to claim 2, characterized in that In step S1, the reaction solvent is at least one of tetrachloromethane, dichloromethane, N,N-dimethyl sulfoxide, and N-methylpyrrolidone, the amount of the reaction solvent is 15 to 35 mL, the halogen is at least one of chlorine, bromine, and iodine, and the amount of the halogen is 1 to 4 mL.

4. The method according to claim 3, characterized in that In step S1, the output power of the microwave reactor is 100-300 W, the reaction temperature is 70-150° C., and the reaction time is 10-60 minutes.

5. The method according to claim 4, characterized in that In step S2, the reaction solvent is at least one of toluene, N,N-dimethylformamide, 1,2-dichloroethane, and tetrahydrofuran, the reaction solvent is mixed with triethylamine, the volume ratio of the reaction solvent to triethylamine is 1:1 to 3:1, the catalyst is tetrakistriphenylphosphine palladium and cuprous iodide, and the molar ratio of the two catalysts is 1:5 to 1:

15.

6. The method according to claim 5, characterized in that In step S2, the long-range conjugated bromine functional building block is at least one of 1,6-dibromopyrene, 2,7-dibromopyrene, 1,8-dibromopyrene, and 1,3,6,8-tetrabromopyrene, and the reaction unit molar ratio of the long-range conjugated bromine functional building block to the alkyne functional building block is 1:1 to 2:

1.

7. The method according to claim 6, characterized in that In step S2, the reaction temperature of the constant temperature continuous reaction is 80-100° C., and the reaction time is 48-84 hours.

8. The method according to claim 7, characterized in that In step S2, the solvents used in the solvent replacement are dichloromethane, chloroform, acetone, deionized water and methanol in sequence, and the solvent used in the Soxhlet extraction is at least one of methanol, chloroform and dichloromethane.

9. The method according to claim 8, characterized in that In step S3, the vacuum drying temperature is 40 to 80°C, the vacuum degree is less than or equal to -0.09 MPa, and the drying time is 6 to 24 hours.

10. A long-range conjugated organic / inorganic gas separation membrane, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Organic conjugated polymer film, its synthetic method and its application

    CN102492117A

  • Conjugated microporous organic polymer hollow sphere as well as preparation method and application thereof

    CN118325080A

  • Method of preparation of ultrathin metal-organic frameworks & uses thereof

    EP4368285A1

  • Functionalized Porous Organic Polymers for Olefin / Paraffin Separations

    US20150190779A1